(untitled) (Journal of Partial Differential Equations, 2015)
" In this paper, we study a class of coupled fractional nonlinear Schr00f6dinger system with periodic boundary condition. Using Galerkin method, the existence of global smooth solution is obtained. We also prove the uniqueness of the solution."